DEVELOPMENT OF E-LABORATORY INSTRUCTION USING MICROSOFT SWAY FEATURES IN ETHNO-STEM LOADED ACID-BASE PRACTICUM - Kartika R Apriliani; Woro Sumarni; Sudarmin Sudarmin (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2024)
Microsoft Sway is a feature that can be used as a practicum learning media to equip the skill lab creativity of students. In this study, an E-laboratory instruction was produced using Microsoft Sway media. E-laboratory instruction is prepared by integrating ethno-STEM. The purpose of this research is to examine the level of feasibility, practicality, and effectiveness of the developed e-laboratory instruction. Model development used a 4D model from Thiagarajan (Define, Design, Develop, and Disseminate), with test subjects being high school students in 11th grade. Data collection techniques used expert validation sheets, user response questionnaires, observation sheets and test questions. The data analysis technique uses percentage descriptive statistics. The study results show that based on the expert’s assessment, e-laboratory instruction is deemed appropriate by both material and media experts. The results of the student response questionnaire showed that the e-laboratory was declared “Very practice”, with a percentage of 86.15% in small-scale tests and 86.33% in large-scale tests. The average of skill lab creativity based on indicators of planning skills, implementation-interpretation skills, also communication skills show a percentage of 87.19. These results indicate that e-laboratory instruction using Microsoft Sway features is feasible, practical, and adequate for acid-base practicum learning.